Role Of Nitrogen, Phosphor, Potassium Fertilizer In Growth And Yield Of The Main Crop Rice Ratoon - Susanti - Diana; Yulhasmir Yulhasmir; Andi Wijaya (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2022)
The role of nitrogen, phosphor and potassium distribution to all the plant tissue. so as to growth promoted the main crop high potential rice ratoon. The objective this research evaluated vegetative growth and productionof rice ratoon national varieties with nitrogen, phosphor, and potassium fertilizer. Using split plot design with three replicate. Varieties (G) main plot (G1: inpari 6, G2: inpari 10 and G3: inpari 29). Fertilizer (P)sub plot (P1= Urea 250 kg ha-1, TSP 100 kg ha-1 and KCl 50 kg ha-1. P2= Urea 300 kg ha-1, TSP 150 kg ha-1and KCl 100 kg ha-1. P3= Urea 300 kg ha-1, TSP 200 kg ha-1 and KCl 150 kg ha-1). The result show that inpari 29 significant in growth and production. The fertilizer treatment of Urea 300 kg ha-1, TSP 150 kg ha-1and KCl 100 kg ha-1 beter forvegetative growth and production. The combine of inpari 29 and 300 kg ha-1, TSP 150 kg ha-1 and KCl 100 kg ha-1 have high production.